2018
DOI: 10.3390/pathogens7020042
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of the CTXM-15 Producing Escherichia coli O25-ST131 Pandemic Clone in Ecuador

Abstract: Our aim was identify of the pandemic B2-ST131 Escherichia coli clone by to the Institute Pasteur and Achtman scheme, and investigate the resistance profile phenotypic-genotypic, with identification of class 1 integron. Of thirty-five ESBL-producing isolates recovered of patients with diagnosis of urinary tract infections (UTI), six E. coli strains serotype O25 were identified with resistance antimicrobial to several groups of antibiotics such as broad-spectrum cephalosporins, fluoroquinolones and aminoglycosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The results showed that 100 lg/mL of the CcAgNps was more effective than 50 lg/mL, in inhibiting the biofilm formation, due to the presence of phytoconstituents and polyphenolic bioactive compound, which were capped and reduced by silver. It has been reported that green silver nanoparticles inhibited the biofilm formation by damaging the bacterial membrane structure and by disrupting quorum sensing [14]. CcAgNps acted as potential quorum quenching compounds which were due to the presence of phytochemical compounds of plant extract incorporated during nanoparticle synthesis [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that 100 lg/mL of the CcAgNps was more effective than 50 lg/mL, in inhibiting the biofilm formation, due to the presence of phytoconstituents and polyphenolic bioactive compound, which were capped and reduced by silver. It has been reported that green silver nanoparticles inhibited the biofilm formation by damaging the bacterial membrane structure and by disrupting quorum sensing [14]. CcAgNps acted as potential quorum quenching compounds which were due to the presence of phytochemical compounds of plant extract incorporated during nanoparticle synthesis [24].…”
Section: Resultsmentioning
confidence: 99%
“…Biophysically characterized colloidal CcAgNps were used to test the efficacy on CTXM-15 positive E. coli and its CTXM-15 gene expression studies. Because ''The CTX-M pandemic'' is E. coli producing CTXM enzyme emerged globally due to onset of UTI's [14]. The most widely distributed is CTXM-15 enzyme which was detected in 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli is the main ESBL‐producing bacterium identified in food products, human and environmental samples worldwide (Rawat and Nair ; Ojer‐usoz et al ). In Ecuador, ESBL‐producing E. coli strains have been characterized in clinical samples, raw vegetables, dog faeces and broiler chickens (Gestal et al ; Ortega‐Paredes et al ; Chiluisa‐Guacho et al ; Soria Segarra et al ; Hedman et al ; Vinueza et al ; Zurita et al ). However, there is no data about the contamination of street food with ESBL‐producing E. coli strains.…”
Section: Introductionmentioning
confidence: 99%
“…Recent Latin American studies have shown an increase in the prevalence of this group of enzymes in E. coli isolates [ 34 , 35 , 36 , 37 ]. In Latin America, clinical isolate studies have been carried out where the dissemination of the ST43/ST131 clone is evidenced in several countries both at the hospital and community level [ 17 , 23 , 24 ], however, in the Central American region there is little data regarding the identification of this clone. Studies have shown a prevalence of E. coli ST131 among non-ESBL-producing isolates of between 10 and 13% [ 8 ], however, in our analyzed strains, all strains belonging to this clone were carriers of ESBL.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies from Latin American countries have described the presence of ST131, both in hospitals and the community [ 19 , 20 , 21 , 22 ]. In Ecuador, a study of E. coli serotype O25 carrying ESBL belonged to ST 131/PST43 and resulted in carriers of CTX-M-15 [ 23 ]. However, to the best of our knowledge, there are still no reports on the molecular epidemiology of infection-causing E. coli strains in Central America [ 24 ].…”
Section: Introductionmentioning
confidence: 99%